PENDIDIKAN ISLAM DALAM PERSPEKTIF AL - QURAN SURAT AL – IMRON AYAT 138 – 139 - Arobi, Ibnul; Sa'diyah, Halimatus (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2019)
Abstract By seeing the existing reality, such as the rise of student brawl, drinking, the spread of drugs and some behaviors that deviate from religious and cultural norms, promiscuity, free sex, sexual abuse makes the role of education increasingly questionable. Education is often used as a scapegoat for failing to be said to have failed in achieving an educational objective, especially Islamic religious education which failed to print insane kamil. Ahmad D. Marimba in his book "Penganta Islam Education" states that the final goal of Islamic education is the realization of Muslim personality. Whereas what is meant by Muslim personality is a personality that has all its aspects, both its external behavior, soul activities, and philosophy of life and its devotion to show dedication to God, surrender to him, From the background of the above problems the writer discusses: How Islamic education in the perspective of the Koran Surat al-Imron verses 138-139. The purpose of this study is to find a picture of Islamic education in the perspective of Q.S Al-Imron verses 138-139. The results of the research conducted by the author is that the Islamic education contained in Surah Al Imron 138-139 is (a) humans can take history from the past from the sunnahs of Allah that applied to humans before. (b) humans can know the straight and true path of hiup where al-quran is the educator and illuminator of the path of human life. (c) in order for humans to be strong and physically and mentally healthy, to be happy and peaceful people to live in this world and the hereafter, and to become people of increasing degrees. (d) For humans to become people who truly believe in God. Keywords: Islamic education which is learned from the Qur'an al-Imron verse 138 -139